2008
DOI: 10.1002/ana.21315
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor antagonist istradefylline (KW‐6002) reduces “off” time in Parkinson's disease: A double‐blind, randomized, multicenter clinical trial (6002‐US‐005)

Abstract: Objective: Based on new understanding of nondopaminergic pathways involved in Parkinson's disease (PD) pathophysiology, a selective adenosine A 2A receptor antagonist, istradefylline, shows promise for the treatment of PD. Methods: Istradefylline (40mg/day) was studied in levodopa-treated PD subjects experiencing prominent wearing-off motor fluctuations. At 23 North American sites, 196 subjects were randomized in a double-blind, 12-week outpatient clinical trial of istradefylline (114 completing the trial) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
203
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(209 citation statements)
references
References 21 publications
(34 reference statements)
2
203
0
4
Order By: Relevance
“…In these studies, istradefylline was utilized as add-on therapy to 1500 PD patients with motor fluctuations and dyskinesia. These studies demonstrated a statistically significant, but modest decrease of 0.7-1.2 h 'off ' time, associated with a similar increase in 'on' time (LeWitt et al, 2008;Stacy et al, 2008). The frequency of dyskinesia in the treated group was actually greater than that observed in the group treated with placebo.…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 75%
“…In these studies, istradefylline was utilized as add-on therapy to 1500 PD patients with motor fluctuations and dyskinesia. These studies demonstrated a statistically significant, but modest decrease of 0.7-1.2 h 'off ' time, associated with a similar increase in 'on' time (LeWitt et al, 2008;Stacy et al, 2008). The frequency of dyskinesia in the treated group was actually greater than that observed in the group treated with placebo.…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 75%
“…Moreover, on the basis of the apparent protective effect of coffee in PD, adenosine receptor (A 2A ) antagonists have also been tested and there is evidence that they improve parkinsonian symptoms in animal models [670] and clinical trials [671][672][673][674]. Lastly, the more recently indicated protective effect of uric acid, together with its ability to slow disease progression, has led to the initiation of a clinical trial of inosine, a precursor that increases uric acid levels.…”
Section: Comments and Perspectivesmentioning
confidence: 99%
“…Potential side effects of A2A receptor antagonists might include increased blood pressure and inflammation. However, based on the results of recent clinical trials with A2A receptor antagonists against Parkinson's disease, A2A antagonists seem to be welltolerated (LeWitt et al, 2008).…”
Section: Extracellular Adenosine Triphosphate and Adenosine J Stagg Amentioning
confidence: 99%